Wildlife Forensics: Current State and Development Perspectives in the Russian Federation - S. A. Smirnova; G. G. Omel’yanyuk; V. V. Gulevskaya; T. V. Perfilova; M. V. Nikulina (Теория и практика судебной экспертизы)
The article notes the necessary preconditions for building a new direction of expert activity in the system of the Russian Ministry of Justice the wildlife forensics. Close attention is paid to the objects of this type of forensic research; typical questions raised before the expert are enumerated; relevant examples from expert practice are given. The author also considers the application of expert prevention activities in wildlife forensics to avoid violations leading to the extinction of rare species of plants and animals. The article also explains the prospects of implementation of DNA testing for the objects of plant and animal origin in wildlife forensics.